Immune mechanisms in chronic kidney disease-mineral and bone disorder: current insights and therapeutic implications - Xu, Bin; Ma, Rui; Wu, Yuqiang; Liu, Chi; Song, Xiangrong (Frontiers in Medicine, 2025)
Chronic kidney disease-mineral and bone disorder (CKD-MBD) is recognized as a systemic syndrome that manifests with a range of complications including mineral dysregulation, skeletal abnormalities, and vascular calcification (VC). Recent research has increasingly pointed toward immune dysregulation as a pivotal factor in the development and progression of this disorder. The current review endeavors to consolidate the latest findings regarding how chronic inflammation, dysfunction of immune cells, and disturbances in the gut-kidney axis contribute to the progression of CKD-MBD. Central to the mechanisms at play are pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and interleukin (IL)-6, which are found to facilitate bone resorption through the activation of the receptor activator of NF-kappaB ligand (RANKL)/receptor activator of nuclear factor-kappa B (RANK)/osteoprotegerin (OPG) signaling pathway. Furthermore, macrophage-induced VC is linked to the activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome. Additionally, an imbalance between osteoblasts and osteoclasts, driven by uremic toxins, exacerbates the skeletal manifestations of the disorder. Despite the availability of current therapeutic options, including phosphate binders and vitamin D analogs, these treatments fall short in adequately addressing the immune-mediated aspects of CKD-MBD, indicating an urgent need for innovative strategies that effectively target inflammatory pathways, inhibit sclerostin, or modulate fibroblast growth factor (FGF)-23 levels. Emerging preclinical studies have shown that sodium-glucose cotransporter 2 (SGLT2) inhibitors and anti-sclerostin antibodies hold significant promise in lessening VC and enhancing bone health. However, translating these findings into clinical application encounters hurdles related to the diversity of patient populations and the dependence on surrogate endpoints for efficacy. This review emphasizes the critical need for incorporating immune-centric strategies into the management of CKD-MBD. It advocates for the development of biomarker-driven, personalized therapies and highlights the importance of conducting longitudinal studies to bridge the existing gaps in knowledge and improve patient outcomes.